K-Owl: Next-Gen Interactive Platform for Student Engagement and Feedback - Nan Cenka, Baginda Anggun; Agnes Audya Tiara P; Ardanisa Rachma; Avelia Diva Zahra; Harry B. Santoso (AI Society & STMIK Indonesia, 2025)
In the digital era, the challenges faced by lecturers and students in learning are increasingly diverse, which makes students tend to be less involved in learning. A student response system called “K-Owl” is proposed to support the Know, Want to Know, Learn (KWL) strategy where lecturers can monitor students’ knowledge in real-time while the platform helps students stay actively engaged in class. User-Centered Design was used as a methodology to ensure that the proposed platform aligns with user needs, with stages including identifying user problems and needs, system design and development, and evaluation. This study involved 16 interview participants and 71 usability testing participants. Quantitative data were collected using the System Usability Scale (SUS) and the Maze application to usability testing and analysed using the SUS Score and Maze Score. Meanwhile, qualitative data were collected through user interviews and analysed using thematic analysis. This study resulted in three main features including courses management, KWL, and dashboard. The results of user acceptance testing and usability testing were with a score of 100% and a SUS score of 69 (Good category), respectively. The results of the study indicate that K-Owl is a promising platform to support active learning.